Access to health care for migrants in French Guiana in 2022: a qualitative study of health care system actors - Brun-Rambaud, Gabriel; Alcouffe, Leslie; Tareau, Marc-Alexandre; Adenis, Antoine; Vignier, Nicolas (Frontiers in Public Health, 2023)
Background: Access to health care is a major public health issue. With 281 million international migrants around the world, population movements are another major issue. Migrants are particularly exposed to precariousness during their migratory journey and after their settlement. These vulnerabilities may have deleterious effects on their health status and on their social conditions. In French Guiana, 36% of the population is of foreign origin. The objective of this study is to explore the barriers and the facilitators to accessing health care for migrants in French Guiana in 2022, from the perspective of health care professionals, social workers and local NGO actors. Methods: This research is an exploratory qualitative study based on the experiential knowledge of health care professionals, social workers and local NGO actors in French Guiana. 25 semi-structured interviews were conducted with these professionals and actors between April and June 2022, using an interview guide to explore their practices, representations and beliefs of access to health care and accompaniment of migrants in their patient journey. The interviews were transcribed and analyzed using the thematic analysis method. Results: Participants highlighted that migrants are exposed to many factors hindering their access to health care in French Guiana (administrative complexity, language barriers, financial barriers, mobility issues, etc.). With the situations of great precariousness and the inadequacies of the public authorities, local NGOs and associations have an important role in providing close support to migrants. Health mediation supports migrants in their social and health care journey to lead them towards empowerment. Health mediators contribute to promote a better understanding between professionals and migrants. Conclusion: This article highlights the issues surrounding access to health care for migrants, associative support and health mediation in the Guianese context, which is marked by significant socio-cultural diversity and precariousness. Considering the benefits of associative support and health mediation, as well as social inequalities in health, is essential for health care professionals, social workers, local NGO actors, associations, public health authorities and political decision-makers to initiate concrete and suitable actions in favor of access to health care and social support for migrants in French Guiana.